Multimedia and cognition: Examining the effect of applying cognitive principles to the design of instructional materials - Thompson, Nik; McGill, T. (Baywood Publishing Company Inc., 2008)
The human cognitive system possesses a finite processing capacity, which is split into channels for various modalities, and learning can be inhibited if any of the cognitive channels is overloaded. However, although the amount of e-learning materials is increasing steadily, the design of instructional material has been largely based on intuition rather than cognitive principles. This research investigated if it is possible to improve the effectiveness of an established e-learning system by the application of cognitive design principles. And if so, does the increased development time and resources yield a substantial effect on learning. Quantitative data collecting during the experiment supported the cognitive principles based design and demonstrated that significantly better quiz scores were obtained in transfer and retention tests when compared against a more traditional design. The results of the study also indicate that the cognitive principles based design was both practical and feasible to apply in terms of necessary resources. © 2008, Baywood Publishing Co., Inc.